Emergency Online Language Education and Academic Integrity - Salim Razı; Özgür Şahan (Literacy Trek, 2021)
The Covid-19 pandemic has underscored the academic integrity when conventional classrooms were replaced by emergency online education. This special issue focuses on how academic integrity relates to emergency online language education. The articles included in this special issue take a small but significant step in promoting educational and research practices related to academic integrity.